School football: the new hope! Exploring the new nationwide system of Chinese sport. Issue 2 (3rd May 2016) - Liu, Tianbiao; Mao, Zhenming; Zha, Ping
Abstract: After the Beijing Olympic Games, people began to rethink the long‐existing sport 'nationwide system' in China in light of the many negative aspects of this system. School football, as a new and prominent product of this system, is playing a pioneering role in reforming the system. This paper analyses the existing problems with the old 'nationwide system' through interviews with field experts and suggests a roadmap to a new system. We take school football as an example of system reform, providing a possible way of not only developing school football itself but also reforming the system.